Schama, Citizens - A chronicle of the French Revolution - Howell, Michael (Teaching History: A Journal of Methods, 1991)
In his preface Simon Schama, a British-born, Cambridge-educated, Harvard history professor, writes that "in Citizens I have tried to bring a world to life rather than entomb it in erudite discourse." He has succeeded, producing a bestseller more popular with general readers than specialists.